Patterns of failure in high-metastatic node number human papillomavirus-positive oropharyngeal carcinoma. (October 2018) - Lee, Nicholas C.J.; Kelly, Jacqueline R.; Park, Henry S.; An, Yi; Judson, Benjamin L.; Burtness, Barbara A.; Husain, Zain A.
Highlights: The number of involved nodes in resected HPV-positive oropharyngeal cancer is a significant predictor of PFS. 5 or more pathologically positive nodes places patients at high risk of both locoregional recurrence and distant metastases. The rate of distant metastases for 5 or more positive nodes is >50%. Abstract: Background: The 8th edition American Joint Committee on Cancer staging system for resected HPV-positive oropharynx carcinoma (HPV+ OPC) highlights high node number as a critical determinant of survival. We sought to characterize outcomes and patterns of failure in patients with high pathologically involved node number oropharynx cancer. Methods: We retrospectively identified 116 HPV+ OPC patients sequentially treated with neck dissection and either resection or intraoperative brachytherapy of the primary tumor between 2010 and 2016. External beam radiation was given based on the pathologic findings. Cox proportional hazards regression was used for multivariate analysis. Results: With a median follow-up of 27 months, the 3-year overall survival and progression free survival (PFS) were 89% and 81%, respectively. On multivariate analysis, ≥5 involved lymph nodes was significantly associated with worse PFS (hazard ratio 4.3, 95% confidence interval (CI) 1.5–12.0, P  = 0.001). Rates of 3-year locoregional recurrence (LRR) in patients with ≤4 vs ≥5 were 6% and 22% (log-rank P  = 0.12). Rates of 3-year distant metastases (DM) were 12% and 53% between ≤4 and ≥5 (log-rank P  < 0.001). Conclusion: Our findings confirm that patients with 5 or more involved lymph nodes appear to have substantially worsened rates of disease recurrence. While these patients appear to be at high risk of both LRR and DM, the predominant mechanism of failure is distant, and the rate of DM in this group was over 50%. Dedicated clinical trials in this patient population are warranted with a focus on mitigating the high DM rate.